2017
DOI: 10.16916/aded.322417
|View full text |Cite
|
Sign up to set email alerts
|

Eğik El Yazısıyla Okuma Yazma Öğrenen Öğrencilerin, Eğik El Yazısına İlişkin Durumları

Abstract: Nitel olarak gerçekleştirilen bu araştırmada 2013-2014 eğitim öğretim yılında eğik el yazısı ile ilkokuma ve yazma öğrenip liseye devam eden 65 öğrencinin eğik el yazısı hakkındaki düşüncelerinin neler olduğu, eğik el yazısı kullanmayı sürdürme durumları, eğik el yazısını kaçıncı sınıfa kadar kullandıkları ve eğik el yazısını bırakma nedenleri incelenmiştir. Araştırma sonucunda 65 öğrenciden bitişik eğik yazı için 22 olumlu 156 olumsuz ifade alınmıştır. Öğrencilerin bitişik eğik yazıyı terk etmeye 3. sınıftan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…In a study with similar findings, Sıcak, Arslan and Ayan (2016) found the attitudes of classroom teachers towards cursive handwriting closer to negative. As a result of the research of Palavan and Gemalmaz (2017), which is also a similar study, 22 positive and 156 negative opinions were observed for cursive handwriting from 65 students. In this respect, the result of this study is in line with the findings of these studies.…”
Section: Resultsmentioning
confidence: 57%
“…In a study with similar findings, Sıcak, Arslan and Ayan (2016) found the attitudes of classroom teachers towards cursive handwriting closer to negative. As a result of the research of Palavan and Gemalmaz (2017), which is also a similar study, 22 positive and 156 negative opinions were observed for cursive handwriting from 65 students. In this respect, the result of this study is in line with the findings of these studies.…”
Section: Resultsmentioning
confidence: 57%
“…The studies done by Arslan and Ilgın (2010), Ateş, Çetinkaya and Yıldırım (2014), Kırmızı and Kasap (2013), Yıldırım and Ateş (2010), Yılmaz and Cımbız (2016), found that most of the classroom teachers did not approve the cursive handwriting instruction. Again, the studies done with teacher candidates (Erdem, Yılmaz and Bozkurt, 2014), students (Palavan and Gemalmaz, 2017) and parents (Coşkun and Coşkun, 2014) were showed same results. One of the reasons why classroom teachers do not agree with the cursive handwriting is that the hand muscles are not developed.…”
Section: Discussionmentioning
confidence: 57%
“…Arslan ve Ilgın (2010), Ateş, Çetinkaya ve Yıldırım (2014, Kırmızı ve Kasap (2013), Yıldırım ve Ateş (2010, Yılmaz ve Cımbız (2016) tarafından yapılan çalışmalarda sınıf öğretmenlerinin çoğunun bitişik eğik yazı öğretimini uygun bulmadıkları belirlenmiştir. Yine öğretmen adaylarıyla (Erdem, Yılmaz ve Bozkurt, 2014), öğrencilerle (Palavan ve Gemalmaz, 2017), velilerle (Coşkun ve Coşkun, 2014) yapılan çalışmalarda da bitişik eğik yazının öğrenciler için uygun olmadığı ortaya konmuştur.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation
“…Studies examining students' acquisition of cursive handwriting, which was removed from the curriculum in 2017, were conducted (Aydın, 2016;Bayraktar, 2006;Coşkun, 2011;Duran & Akyol, 2010;Duran, 2009;Erdoğan, 2012;Kadıoğlu, 2012b;Memiş & Harmankaya, 2012;Özdemir, 2014;Özkaya & Ataş, 2015;Palavan & Gemalmaz, 2017;Uysal, 2013;Yılmaz & Çakır, 2015). Some of these studies (Acat & Özsoy, 2006;Bayraktar, 2006;Şahin, 2012) focused on the problems experienced by students in writing upper and lower case letters in cursive handwriting and identified misspelled letters.…”
mentioning
confidence: 99%